Age and years to death disparately influence reproductive allocation in a short‐lived bird. Issue 9 (22nd August 2017) - Tarwater, Corey E.; Arcese, Peter
Abstract: Theory predicts that reproduction will change as individuals near the end of their lives by either increasing reproductive allocation (terminal allocation hypothesis) or decreasing allocation (senescence hypothesis) toward the end of life. Although senescence has received more support, few studies examine how both age and years to death influence late‐life reproduction. We used a 37‐yr study of Song Sparrows ( Melospiza melodia ) to ask how age and years to death influenced reproductive allocation late in life. We observed both senescence and terminal allocation, and that age and years to death interacted to influence individual variation in allocation tactics. In particular, we observed a decline in allocation in older individuals (senescence), but only when comparing individuals with the same number of years to death. Likewise, we observed terminal allocation, but only in young females. Reproductive tactics were most variable in young females, with many exerting high effort but living 1–2 yr, and others exerting low effort annually and living longer. Our results suggest that late‐life reproductive tactics are influenced by both chronological age and years to death, and that short‐ and long‐lived females with differing reproductive tactics exist within this population of Song Sparrows.